Cohort Profile: Gachon Regional Occupational Cohort Study (GROCS) - Wanhyung Lee; Yongho Lee; Junhyeong Lee; Uijin Kim; Eunsun Han; Seunghon Ham; Won-Jun Choi; Seong-Kyu Kang (Elsevier, 2022)
Background/Aims: The Gachon Regional Occupational Cohort Study (GROCS) is a large-scale longitudinal study of occupational safety and health data (covering Work Environment Monitoring, Workers' Health Surveillance, and Occupational Health Service) conducted by the Gachon University Gil Medical Center (GUGMC) in Incheon, Republic of Korea. We conducted GROCS to identify the health effects of workers' occupational risks, behavior, socioeconomic status, and life style. Methods: The GROCS includes data from Work Environment Monitoring, Workers' Health Surveillance, and Occupational Health Service. The baseline year for all data collection was 2018. Work Environment Monitoring was conducted in 240 companies located in Incheon. General Health Examination and Special Health Examination were performed on 32,725 and 9,504 workers, respectively. Occupational Health Services were provided to 16,883 workers in 171 companies. These data have been collected and operated at an external data management institution and were provided as a retrospective cohort after removing personal identification information. Results: In 2018, the total number of companies was 2,854, among which which 488 special Health Examination, 171 Work Environment Monitoring, and 240 Occupational Health Service. The proportion of companies undergoing Special Health Examination was 17.1%, the proportion of companies undergoing Work Environment Monitoring was 8.4%, and the proportion of Companies undergoing Occupational Health Service was 6.0%. Conclusion: GROCS expects researchers to utilize its useful and reliable resource for occupational health and surveillance with for academic or political purposes to lead to improved workers' health and working environment.